Polemics about Women's Leadership from a Modern Islamic Perspective - Dawam, Mohammad; Miryan, Zulaiha; Muthmainah, Siti (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2023)
Women's leadership in the political arena reaps controversy in Islam. This is due to the authentic hadith which states that a people will not be lucky if they are led by women. For conservative scholars, they will understand the hadith as it is (textual). However, moderate scholars will understand it from a contextual perspective. The Islamic religion is guided by the Qur'an and hadith, therefore, it would be unfair if you only take pictures from the side of the hadith and ignore the al-Qur'an. This article will discuss women's leadership from the perspective of the Al-Qur’an, hadith, women's biology and the sociology of the Indonesian nation. The conclusion of this article is that the Al-Qur’an legitimizes women's leadership through the story of the queen of Saba' (Bilqis). The hadith about women's leadership can be understood as the Prophet's 'comment' on the change of leadership in Persia and has a local-temporal content. Women have biological weaknesses during menstruation and pregnancy, physical weaknesses compared to men, psychological and emotional weaknesses. Meanwhile, the Indonesian nation actually adheres to patriarchy. So, political contestation is wide open to anyone, regardless of gender. Whoever is the best, he has the right to be a leader.